Treatment and analysis of a case of pulmonary embolism with pulmonary infarction following mixed haemorrhoid surgery case report - Yanfeng Xu; Yakun Wu; Zhanglong Cong (Medicine, 2026)
Rationale: Pulmonary embolism following mixed hemorrhoid surgery is uncommon, with few such cases reported in domestic and international literature. This study examines the clinical characteristics, diagnosis, treatment, and outcomes of pulmonary artery embolism after mixed hemorrhoid surgery, aiming to enhance clinicians’ vigilance and prevention of postoperative complications. Patient concerns: Clinical features of a patient with pulmonary embolism following mixed hemorrhoid surgery, admitted to the Department of Anorectal Surgery at Ansteel General Hospital in June 2025, were analyzed. A 55-year-old female presented with a rectal mass protruding after defecation for approximately 2 weeks. Denies a history of hypertension or diabetes; denies a history of infectious diseases such as hepatitis or tuberculosis; no history of surgery or trauma; no history of varicose veins or swelling and pain in both lower extremities; no history of cardiovascular or cerebrovascular disease or thrombosis; and has had sleep disturbances for over a year. She underwent mixed hemorrhoid surgery on June 24, 2025 and was discharged uneventfully. Five days later, the patient presented to our hospital’s respiratory medicine department with sudden right-sided chest pain accompanied by dry cough. Pulmonary computed tomography (CT) angiography revealed pulmonary embolism with pulmonary infarction. Abnormalities in D-dimer, fibrinogen, and blood gas analysis. Diagnoses: Combined with the patient’s symptoms and physical findings, led to a definitive diagnosis of pulmonary embolism with pulmonary infarction following mixed hemorrhoid surgery. Interventions: Following oxygen therapy, anti-inflammatory treatment, and anticoagulation, a follow-up pulmonary CT scan demonstrated reduced pulmonary infarction with improved lesion margins. Outcomes: Prognosis is favorable, with the patient currently undergoing regular follow-up. Lessons: Although the risk of pulmonary embolism following hemorrhoid surgery is low, if it does occur and is not promptly diagnosed and treated, the consequences are often severe and may even be life-threatening. This article presents the diagnostic and treatment process for this case and provides analysis and discussion in conjunction with related cases, with the aim of providing some advice for the timely diagnosis and treatment of pulmonary embolism following colorectal surgery.